Congestion‐aware HTTP adaptive streaming system over SDN‐enabled Wi‐Fi network. (26th April 2019) - Noh, Hyunmin; Lee, Hwanwook; Go, Yunmin; Park, Hyun; Lee, Jongman; Kim, Jaewoo; Song, Hwangjun
Summary: This paper proposes a novel congestion‐aware HTTP adaptive streaming (HAS) system to improve video quality of clients over software‐defined network (SDN)–enabled Wi‐Fi network. The proposed system employs SDN technology to efficiently control the network resources and video quality over the competing Wi‐Fi network. In the proposed system, an SDN‐enabled access point (AP) can monitor the streaming status of clients, such as the buffered playback time and information of requested segments. An SDN controller collects not only the streaming status of clients but also the Wi‐Fi network conditions from the AP using OpenFlow. Additionally, when a congestion is going to occur, it determines the segment bitrate of each client to provide seamless and high‐quality streaming services. The proposed system is fully implemented using open‐source programs, such as ONOS and hostapd, and is examined in a real Wi‐Fi network. The experimental results verify that the proposed system can provide seamless and high‐quality HAS services for the clients compared with existing systems.